Effects of different remineralizing agents on color stability and surface characteristics of the teeth following vital bleaching - Bilge, Kubra; Kilic, Vahti (Wiley, 2021)
The aim of the study was to investigate the effects of various remineralizing agents on the color stability and surface characteristics of the teeth after vital bleaching. The extracted 96 human incisors were used for the study. Initially, the samples were randomly divided into two groups and exposed to in-office and at-home bleaching agents. Then, the groups were divided into six subgroups (n = 8), including the control group did not undergo remineralization after bleaching, according to five remineralizing agents (Gelato APF Gel, Remin Pro, Tooth Mousse, MI Paste Plus, Curodont Protect). Surface roughness was assessed at baseline, after bleaching and remineralization procedures. Color measurements of the samples were obtained at baseline, after bleaching and then after immersion in the staining solution following remineralization process. Scanning electron microscopy and atomic force microscopy (AFM) analyzes were carried out in order to examine the morphological changes on the surface of the enamel. The independent t-test, paired-samples t-test, and one-way ANOVA was used to compare the data and post-hoc LSD test to compare the difference among the study groups (alpha = .05). Surface roughness increased following in-office and at-home bleaching in all groups, and reduced after application of remineralizing agents in all groups. Significant differences were found among the groups with respect to changes in surface roughness and color values following treatment with remineralizing agents (p <.05). AFM analyses revealed increased surface roughness after bleaching and a reduction of rough surfaces following treatment with remineralizing agents. Remineralizing agents can be used to reduce postbleaching increase in surface roughness and to maintain color stability after bleaching.
Keywords: AFM; color stability; remineralizing agents; surface characteristics; vital bleaching